P‐117: Simulation of Light Extraction from an Electroluminescent QD‐LED. Issue 1 (29th May 2019) - Montgomery, David J.; Boardman, Edward A.; Dimmock, James A. R.; Smeeton, Tim M.
Abstract : We use Finite Difference Time Domain (FDTD) methods to simulate light extraction from bottom emitting and top emitting electroluminescent quantum dot LEDs (QD‐LEDs) and observe good correlation with experimental results. The simulations are used to design QD‐LED display sub pixels for high external quantum efficiency and low color shift.